Eficacia de fármacos hipoglucemiantes en Diabetes Mellitus tipo 2 en la Clínica de Especialidades Mogrovejo, Loja - Sarango Martínez, Xavier Alexander (2020)
Introduction: Diabetes Mellitus Type 2 is one of the chronic degenerative diseases with the highest prevalence in the world and in our country. With the rise of new drugs with different mechanisms of action to achieve excellent glycemic control, the drug of choice is metformin; but monotherapy does not achieve good glycemic control, for which it is necessary to add a second drug to the treatment, such as inhibitors of dipeptidyl peptidase -4 (iDPP-4) or inhibitors of the cotransporter type 2 sodium glucose (iSGLT-2 ). Methodology: it was a study with a quantitative, descriptive, retrospective, longitudinal approach, in which fasting glucose and glycosylated hemoglobin were analyzed before starting and after three months of dual pharmacological treatment and the two pharmacological regimens were compared, 83 were included patients with Diabetes Mellitus. Type 2 Results: It was observed that the patients were older than 65 years of age and female, after three months of treatment with metformin plus sitagliptin the mean fasting glucose value was 136.3 mg / dL and glycosylated hemoglobin was 8.11%; with metformin plus empagliflozin, fasting glucose was 138.9 mg / dL and glycosylated hemoglobin was 8.01%, there were statistically significant differences. Conclusion: there was efficacy in the dual hypoglycemic regimens by reducing fasting glucose and glycosylated hemoglobin levels after three months of treatment with a statistically significant difference; but when comparing the two schemes there was no difference. Key words: Diabetes, metformin, dipeptidyl peptidase -4 inhibitors (iDPP-4), type 2 sodium glucose cotransporter inhibitors (iSGLT-2), glycosylated hemoglobin.